Search for flavour-changing neutral tqH interactions with H → γγ in pp collisions at √s = 13 TeV using the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Journal of high energy physics, 2023)
A search for flavour-changing neutral interactions involving the top quark, the Higgs boson and an up-type quark q (q = c, u) is presented. The proton-proton collision data set used, with an integrated luminosity of 139 fb−1, was collected at $$ \sqrt{s} $$= 13 TeV by the ATLAS experiment at the Large Hadron Collider. Both the decay process t → qH in $$ t\overline{t} $$production and the production process pp → tH, with the Higgs boson decaying into two photons, are investigated. No significant excess is observed and upper limits are set on the t → cH and the t → uH branching ratios of 4.3 × 10−4 and 3.8 × 10−4, respectively, at the 95% confidence level, while the expected limits in the absence of signal are 4.7 × 10−4 and 3.9 × 10−4. Combining this search with ATLAS searches in the H → τ+τ− and H → $$ b\overline{b} $$final states yields observed (expected) upper limits on the t → cH branching ratio of 5.8 × 10−4 (3.0 × 10−4) at the 95% confidence level. The corresponding observed (expected) upper limit on the t → uH branching ratio is 4.0 × 10−4 (2.4 × 10−4).
*The ATLAS collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, F. Del Rio, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H.-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und sehr viele weitere Personen]
Gesehen am 08.08.2024
Im Titel steht der Buchstabe s unter dem Wurzelsymbol